2021
DOI: 10.1016/j.ajic.2020.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged persistence of PCR-detectable virus during an outbreak of SARS-CoV-2 in an inpatient geriatric psychiatry unit in King County, Washington

Abstract: Highlights SARS-CoV-2 is an important cause of health care-acquired infection. Asymptomatic SARS-CoV-2 infection was common in this cohort of elderly individuals. Duration of PCR positivity was similar among symptomatic and asymptomatic patients. Virus cycle thresholds were similar among symptomatic and asymptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
(57 reference statements)
0
16
0
1
Order By: Relevance
“…Testing for SARS-CoV-2 has predominantly been performed on molecular platforms with exquisite analytical sensitivities that can detect fewer than 100 viral RNA copies per ml of viral transport medium (VTM) ( 1 ). These analytical sensitivities result in the detection of low-level shedding in patients for weeks to months after initial infection, often with very low viral loads ( 2 5 ). A double-edged sword of the sensitivity offered by real-time reverse transcription-quantitative PCR (qRT-PCR) is the possibility that the molecular methodology detects RNA copies of virus that may not necessarily correlate with an active infection, especially if the result is a low viral load ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Testing for SARS-CoV-2 has predominantly been performed on molecular platforms with exquisite analytical sensitivities that can detect fewer than 100 viral RNA copies per ml of viral transport medium (VTM) ( 1 ). These analytical sensitivities result in the detection of low-level shedding in patients for weeks to months after initial infection, often with very low viral loads ( 2 5 ). A double-edged sword of the sensitivity offered by real-time reverse transcription-quantitative PCR (qRT-PCR) is the possibility that the molecular methodology detects RNA copies of virus that may not necessarily correlate with an active infection, especially if the result is a low viral load ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…They followed the provided checklist but focused on the larger picture of reducing cross-contamination (CDC, 2020). Developing a culture of best practice also required peer accountability and engagement of staff in preventing the further spread of SARS-CoV-2 (Corcorran et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The information presented in this article is based on a retroactive review of staff engagement and enhanced infection control practices that led to the containment of an outbreak of SARS-CoV-2 that occurred from March 11 to May 5, 2020, in an inpatient geriatric psychiatric unit with separate, but adjacent, locked East and West wings in King County, Washington. More detailed methods regarding the outbreak identification, repeat testing, and detection of viral shedding in SARS-CoV-2 have been previously described (Corcorran et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While symptomatic carriers have much higher transmissibility probabilities compared with asymptomatic carriers, recent studies found little to no difference in viral load between pre-symptomatic, asymptomatic, and symptomatic patients. 19-23 However, asymptomatic carriers could have faster clearance. 17,24 For example, Yang et al 18 reported a median duration of viral shedding of 8 days (interquartile range [IQR]: 2–12) for asymptomatic and 19 days (IQR: 16–24) for symptomatic carriers.…”
Section: Methodsmentioning
confidence: 99%